MULTI-PERSON DECISION FOR SUSTAINABLE DESIGN ON IBS FLOOR SYSTEM SELECTION - Christiono Utomo; N.A. Rahman; A. Idrus (Journal of the Civil Engineering Forum, 2012)
Selecting a design solution (choice problem) is one of the natures of design decision. If the problem is more complex and involves multi participants, decision aid is necessary. This paper discusses the nature of group judgment and negotiation on multi-criteria decision-making methodologies. It presents a conceptual model of negotiation support in a multi-person decision on building floor system selection. Decision technique (AHP) was applied for decision process in a satisfying options and game theory for coalition formation. An n-person cooperative game is represented by a set of all players. The proposed coalition formation model enables each agent to select individually or coalition. It improves the value of building system decision. It further emphasizes the importance of performance evaluation in the design process and value-based decision. The support model can be extended to an automated negotiation and in different building system selection with proper  modification. Keywords: Multi-person, design decision, IBS, floor system selection.